2013
DOI: 10.1186/2193-1801-2-114
|View full text |Cite
|
Sign up to set email alerts
|

Edge-interior differences in the species richness and abundance of drosophilids in a semideciduous forest fragment

Abstract: Habitat fragmentation is the main cause of biodiversity loss, as remnant fragments are exposed to negative influences that include edge effects, prevention of migration, declines in effective population sizes, loss of genetic variability and invasion of exotic species. The Drosophilidae (Diptera), especially species of the genus Drosophila, which are highly sensitive to environmental variation, have been used as bioindicators. A twelve-month field study was conducted to evaluate the abundance and richness of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Em um estudo realizado no domínio do Cerrado Brasileiro Emerich (2011) comparou a abundância de drosofilídeos em áreas de vegetação nativa e áreas de monocultura de soja, observando maior abundância de espécies exóticas nas plantações. O autor salienta, em concordância com outros estudos (Penariol;Madi-Ravazzi, 2013), que as espécies exóticas de drosofilídeos estão mais associadas a ambientes secos e quentes. No nosso estudo o ambiente mais seco e quente é a plantação de eucaliptos, o que pode justificar a maior abundância de espécies exóticas neste local.…”
Section: Resultsunclassified
“…Em um estudo realizado no domínio do Cerrado Brasileiro Emerich (2011) comparou a abundância de drosofilídeos em áreas de vegetação nativa e áreas de monocultura de soja, observando maior abundância de espécies exóticas nas plantações. O autor salienta, em concordância com outros estudos (Penariol;Madi-Ravazzi, 2013), que as espécies exóticas de drosofilídeos estão mais associadas a ambientes secos e quentes. No nosso estudo o ambiente mais seco e quente é a plantação de eucaliptos, o que pode justificar a maior abundância de espécies exóticas neste local.…”
Section: Resultsunclassified
“…In this study, we hypothesize that sources of light gradients may also create strong selective pressures and isolation mechanisms that in turn lead to speciation events or stabilizing selection for opposing phototaxis within otherwise overlapping habitats, such as arboreal forests. These forest microhabitats have been addressed previously as sources for spatial separation between species, including studies directly related to the field-sampling of members of the family Drosophilidae [13,25,26], often with the division of species occurring in proximity to the forest edge. While the evolutionary selective pressures and their effects on the relative size of various components of the nervous system have not been previously examined, it has been suggested that sources of light may be one of the ambient forces driving the observed tradeoff in the evolution of these two sensory structures [2].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have addressed microhabitat variation and its effects on species richness or biodiversity. Moreover, that plant hosts and other nutritional resources such as fungi and yeasts can differ greatly between forest edge and forest interior [26,29,33,35]. Thus, it is well recognized that flora and fauna can vary in both their relative abundance as well as their innate preferences across microclimates within a single habitat, where the fitness of a species is intimately tied to its ability to compete for resources within its own environmental niche.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been developed to determine how edge effects act on forest fauna. Among them we can mention Ribas et al (2005), with ants and crikets; McGeoch and Gaston (2000), Ferraz et al (2010a), Copatti and Gasparetto (2012), Penariol and Madi-Ravazzi (2013), and Cabrini et al (2013) with Diptera. The latest analysed richness and composition of Calliphoridae fauna in an Atlantic Forest fragment, and indicated Mesmebinellinae as a sort of bioindicator.…”
Section: The Influence Of Fragmentation and Edge Effectsmentioning
confidence: 99%